Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Neurosains Spiritual - Heni Listiana; Achmad Yusuf; Supandi; Moh. Wardi (Universitas Yudharta Pasuruan, 2021)
Islamic education learning must be developed in spiritual neuroscience. Islamic education has a close relationship with spiritual neuroscience. This interdisciplinary study will provide a broader profile and find new alternatives in the development of Islamic education. This research is interdisciplinary with a literature approach. The data source is in the form of a number of literatures on the Islamic education curriculum and spiritual neuroscience. The data is obtained by documentation. The analysis uses content analysis. The results of this study are: (a) neurospiritual operators related to creative potential (b) these operators can build spiritual learning (c) Neuroscience (spiritual neuroscience) can build the social structure of society (d) This discipline is able to develop the basis of student learning abilities (e) The prefrontal cortex plays an important role in improving memory skills (f) the neuroscience approach through memory skills affects learning outcomes (g) optimizing brain power can be taken in very various ways and processes. Second, there are five foundations for developing Islamic education curriculum based on spiritual neuroscience, they are: philosophical, religious, psychological, and neurophysiological foundations. The third, the approach is used to developing the Islamic education curriculum based on spiritual neuroscience is an integrated approach.